PERSEPSI BADAN OTONOM PELAJAR ISLAM INDONESIA (BO PII) WATI SUMSEL TERHADAP BERITA CROSSHIJABERS CNNINDONESIA.COM - Syarifah Adawiyah; Aliasan Aliasan; Ahmad Harun Yahya (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2020)
This thesis is the result of research describing how the perception of Badan Otonom Pelajar Islam Indonesia (BO PII) Wati on crosshijabers news on Cnnindonesia.com. The presence of crosshijabers or men dressed in syar'i is considered unsettling because it can gives a bad stigma for Muslim women. Therefore, researchers are interested in raising the title